(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The integration of mass media (mass media) and information and communication technologies (ICT) into political processes is analyzed. As effective institutional mechanisms of political communication, they strengthen the interaction between the state, society and citizens. In particular, media platforms and digital systems actively participate in elections, referendums and political projects put up for public discussion, serving to raise political awareness and culture.